Characterization of complete chloroplast genome of Angelica sinensis (Apiaceae), an endemic medical plant to China. Issue 1 (2nd January 2019) - Tian, Enwei; Liu, Qianqian; Chen, Wenna; Li, Fang; Chen, Aimin; Li, Chan; Chao, Zhi
Abstract: Angelica sinensis is a famous traditional Chinese medicinal herb which is used with a long history in China. However, presently, it is on the verge of extinction due to over-exploitation and habitat destruction. To conduct population genomic studies and offer strategies of conservation and management, we sequenced the complete chloroplast genome of A. sinensis using the next-generation sequencing technology. The complete cp genome is 142, 822 bp in length, which contains a large single-copy region (LSC) of 99, 964 bp, a small single-copy (SSC) region of 17, 750 bp, and two inverted repeat (IRa and IRb) regions of 12, 554 bp. The G + C content of cp genome is 37.4%. The genome comprises a total of 128 genes, including 83 protein-coding genes, eight ribosomal RNA(rRNA) genes and 35 transfer RNA (tRNA). Phylogenetic inference indicated that A. sinensis was closely related to A. gigas, A. decursiva, A. nitida and A.dahurica.